Designing a research project - Verschuren, Piet, ....-; Doorewaard, Hans, ....- (The Hague : Eleven International Pub., 2010)
The primary goal of Designing a Research Project is to assist graduate students, PhD candidates and research fellows to develop an effective research design. In addition this book offers supervisors and tutors an opportunity to tighten their grip on their counseling roles while enabling them to perfect their students progress and help them to achieve better research results. Both practice-oriented and theory-oriented research can benefit from applying the methodology used when designing a research project. Designing a Research Project provides insights, guiding principles and methodology for developing a transparent conceptual and technical design for a research. The guiding principles for the conceptual design or research issue help to formulate an attainable and effective research objective, to outline a clear research framework and to determine relevant research issues. The technical design concerns the selection of an adequate research strategy, the different ways of collecting data or information required and the making of a research plan.
Translation of the 4th edition, 2007.
Keywords: Methodologie; Research